TECHNOLOGICAL POTENTIAL OF REED AS BIOMASS FOR BRIQUETTING - Cosereanu, Camelia; Budau, Gavril; Lica, Dumitru; Lunguleasa, Aurel; Gheorghiu, Constantin-Radu (OAIMDD - EcoZone Publishing House, 2011)
In this paper the study on the possibilities of converting chopped reed stalk biomass into briquettes is described, in the conditions of harvesting water reed plant from Danube Delta region in winter time and based on briquetting technology used for wood waste from production. The water reed tested in the research has been harvested from Tulcea reed bed, one of the largest in Romania, chopped in a veneer drum chipper and compacted into the hydraulic briquette machine. The paper focuses on the determination of reed particles characteristics: particle size and particle size distribution with sieving methods and total moisture content, in order to establish the basic conditions in which the reed particles can be compacted into briquettes with high density. The results of the investigations of the authors on the actual technology to be applied for the densification of reed plant into briquettes give precise data about the equipment, technological parameters and basic characteristics of the particles.
Keywords: Biomass; Briquettes; reed; technology